PENGARUH MODEL DISCOVERY LEARNING TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN IPS TERPADU MTs MIFTAHUL ULUM SITUBONDO - Kiptiatul Hasanah; Nursalam Nursalam (STKIP PGRI Situbondo, 2020)
This study aims to determine the effect of the discovery learning model on student learning outcomes in the Integrated Social Studies subject Class VII A at MTs Miftahul Ulum Situbondo. This study used a one-shot case study design. The subjects of this study were Class VII A, with a total of 30 students. They were collecting data using test instruments, observation and interviews. The results of the test instruments were tested by t-test. The analysis result shows that tcount> ttable is 3,814> 2,045. So it can be concluded that there is an average difference between the pretest and posttest learning outcomes. Which means that there is an effect of the discovery learning model on student learning outcomes in the Integrated Social Studies subject Class VII A at Mts Miftahul Ulum Situbondo.